Behavioral changes in frontotemporal dementia: a case report (Portuguese Journal of Family Medicine and General Practice, 2017)
Introduction: Frontotemporal dementia is characterized by changes in personality, behavior, and language. Atrophy of the frontal and temporal cortex is the main pathological finding. As this entity is under-diagnosed, it is important to raise awareness of the difficulties in diagnosis and management. Case Description: A 74 year-old man had progressive changes in appropriate social behavior from age 66. This included a lack of impulse control, inadequate food behaviors and rituals, and reduced production of speech. Some time after the onset of symptoms and consultation with different medical specialists, he was referred to a neurologist who made the diagnosis of frontotemporal dementia. Commentary: The family physician can play an important role by suspecting this condition, through longitudinal care and personal knowledge of the patient. Proper investigation and appropriate and timely guidance can help avoid unnecessary and potentially harmful treatments. The family physician can also manage associated comorbidity and support the family and other caregivers.
Keywords: Frontotemporal Dementia; Behavioral variant of Frontotemporal Dementia; Diagnosis; Therapeutics; Primary Care.